jiwbp - Andi Azikin; Soma Atmaja H. (Jurnal Ilmiah Wahana Bhakti Praja, 2019)
Starting from the strategic position of the Tangerang Regency as a buffer for the Capital City of DKI Jakarta, it later developed into a part of the Greater Jakarta Metropolitan Area (Jakarta, Bogor, Depok, Tangerang and Bekasi), making this region a role as a center for industry, trade and services. Then grow large-scale settlements as a new city in Tangerang Regency. The presence of the role of local government with the function of service, development and Empowerment (Ryas Rasyid, 2001), is so central as an agent of change. Moreover, the presence of these new cities left a socioeconomic impact on the surrounding community, and made extraordinary social changes for the people of Tangerang Regency. The purpose of this study is to analyze the development policies of new cities and analyze how the role of the Tangerang District Government in increasing the capability of the community in tackling the impacts of new city development and social change in the Tangerang Regency. So by using a qualitative research methodology that uses descriptive analysis techniques Triaguasi namely a combination of interviews, documentation and observations carried out continuously, then analyzed so that this study can make conclusions (conclusions, drawings / verivication) and recommendations as a research suggestion.The results of this study conclude that the construction of new cities in Tangerang Regency only increases economic growth, not equity. The quality of human resources affected by the new city is still lagging behind, namely the development of the city, not for the welfare of the surrounding community. Although the role of the local government in empowering the affected people’s economy to improve the capabilities of the community is already strong enough with diverse efforts. As a result, the construction of new cities radically changed community institutions, social systems and patterns of community behavior. New city development presents global culture in Tangerang Regency, Banten Province.